ADVOCACY IS IMPORTANT INSTITUTE IN DEFENSE HUMAN RIGHTS AND FREEDOMS - Valisher Davlyatov (Scholar Express Journals, 2023)
The article analyzes the issues of ensuring the organizational independence of the bar institute from a scientific and theoretical point of view, and it is scientifically and theoretically based that it is the primary condition for the existence of the bar institute. It describes the principles and guarantees of the legal institute. The role of the Advocacy Institute in the life of the state and society, the fact that it is an integral part of the legal system, as well as scientific-theoretical and practical proposals for ensuring the organizational independence of this institute are given. Also, proposals aimed at improving the legal foundations of the bar institute were put forward.
Keywords: advocacy; advocacy activities; Chamber of Advocates; guarantees of independence